DNA methylation: a review of new perspectives for early detection of cervical can cer - Carvalho, Maria Cristina de Melo Pessanha; Rocha, Maria Paula Leite da (Brazilian Journal of Sexually Transmitted Diseases, 2022)
Introduction: Cervical cancer is a serious public health problem and the fourth most common type of cancer in the female population. Persistent human papillomavirus infection is a risk factor for this tumor. However, epigenetic abnormalities occur in the carcinogenic process, in which DNA methylation is an important mechanism for gene silencing. That tends to lead to premalignant changes, a fact which can be investigated through the use of biomarkers for early detection and prevention of cervical cancer. Objective: To identify studies that analyzes epigenetic science, DNA methylation, and research on molecular biomarkers as new perspectives for early detection of cervical cancer. Methods: This is a literature review including articles published in the last 5 years in English and Portuguese, using the LILACS, Medline, SciELO, Cochrane Library, and PubMed databases. Results: The study determined a process of convergence in the analyzed subject. After reading various studies on DNA methylation and cervical cancer, the team highlighted the inactivation of tumor suppressor genes and the activation of oncogenes, which have an important role in cervical carcinogenesis, caused by epigenetic changes found in women with cervical intraepithelial neoplasia and cervical cancer. Conclusion: This review showed several screening strategies associated with cytological and molecular tests; however, there are knowledge gaps and the need for further investigation. Potential biomarkers are suggested to allow the monitoring of molecular events that complement the program of cervical cancer control, reducing mortality in the female population.